TREASURE MAKER'S MOTIVATION TO LOVE TREASURE BOYBAND - Rohana, Viny Septin (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2024)
ABSTRACT The study aims to identify and analyze the factors that motivated Treasure Maker to become a fan of the South Korean boyband Treasure, which, under the umbrella of YG Entertainment, has gained global popularity since its debut in 2020. These boy bands are known for their dedication to their careers, despite facing a variety of challenges, including changing members. Treasure fans, known as the Treasure Maker, showed strong loyalty and regarded the boyband as a source of inspiration. The study uses a qualitative approach with in-depth interview methods and content analysis to collect data from Treasure Maker members in Indonesia. The results show that the key factors that motivate Treasure Makers are the dedication and hard work of Treasure members, the quality of their music and appearance, as well as the positive interaction between boy bands and fans. Moreover, treasure makers feel motivated by the positive messages delivered through treasure songs, which encourage them to pursue their dreams and face life's challenges. The research is expected to provide a deeper understanding of the motivation of K-Pop fans and their contribution to Indonesian fan culture. Keywords: Motivation, Treasure Maker, boyband Treasure, K-pop Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis faktor-faktor yang memotivasi Treasure Maker dalam menggemari boyband Treasure. Treasure, boyband asal Korea Selatan di bawah naungan YG Entertainment, telah meraih popularitas global sejak debutnya pada tahun 2020. Boyband ini dikenal karena dedikasi mereka dalam berkarya, meskipun menghadapi berbagai tantangan termasuk perubahan anggota. Penggemar Treasure, yang dikenal sebagai Treasure Maker, menunjukkan loyalitas yang kuat dan menganggap boyband ini sebagai sumber inspirasi. Studi ini menggunakan pendekatan kualitatif dengan metode wawancara mendalam dan analisis konten untuk mengumpulkan data dari anggota Treasure Maker di Indonesia. Hasil penelitian menunjukkan bahwa faktor-faktor utama yang memotivasi Treasure Maker adalah dedikasi dan kerja keras anggota Treasure, kualitas musik dan penampilan mereka, serta interaksi positif antara boyband dan penggemar. Selain itu, Treasure Maker merasa termotivasi oleh pesan-pesan positif yang disampaikan melalui lagu-lagu Treasure, yang mendorong mereka untuk mencapai impian dan menghadapi tantangan hidup.